Banking on sustainability: structural adjustment and forestry reform in post-Suharto Indonesia - Barr, C. (WWF Macroeconomics Program Office and CIFOR, 2001)
In 1997, a major financial crisis struct Asia. In the wake of that crisis, the International Monetary Fund and the World Bank provided large loans to the Indonesian government in return for their commitment to implement policy reforms intended to stabilize the economy and rekindle growth. Those reforms included various measures explicitly designed to improve forest management, most of which focused on forest concessions run by large Indonesian conglomerates. This book contains analysis on the prospects for policy interventions aimed at promoting sustainable forest management in three important arenas: 1. HPH concession management and timber trade. 2. Pulp and paper expansion and financial risk assessment. 3. Corporate debt resolution.